A study about Protective Effect of Brevibacillus laterosporus texasporus Culture on Broiler Chickens Infected with Salmonella Pullorum - Purba, Mhd Adanan; Shoaib Ahmed Pirzado; Huiyi Cai; Tesfay Hagos Haile; Aijuan Zheng; Jiao Liu; Jiang Chen; Guohua Liu; Nurzainah Ginting; Yunilas (Publisher Cv. Inara, 2020)
A demand for chicken-meat is growing enormously which requires intensification in the production, so it iscrucial to improve the chicken health condition.The aim of this study is to investigate the effects of Brevibacillus laterosporus texasporus culture (BT) to the growth, immunity and blood parameters of broilers and also to determine whether the culture has a potential to act as a probiotic supplement of the fodder. A total of 300 one-day-old male Arbor Acres broilers chickens were randomly assigned to 5 treatments with 6 replications (10 individualsin each replicate) i.e.the positive control (PC)which had no challenge ofSalmonella Pullorum wasadministered inthe basal diet. Meanwhile, the negative control (NC) challenged by Salmonella Pullorumper os was administered in three form of diets, and these were included inthe diet with the composition of kitasamycin for 10 mg/kg as antibiotics growth promotor, BT for 50 mg/kg, and BT for 100 mg/kg. The live body weight (LBW) and average daily body weight gain (ADG)of initial period were upregulated(P<0.05), while at the end of the period, the results displayed the changes in LBW(P=0.304) and ADG (P=0.672). Based on the analysis of Enzyme-linked immunosorbent assay (ELISA), the IgG (g/L) showed no significant values, and the IgM(g/L) significantly rose after 21 days, while the IgA (g/L) showed significant values after 42 days. The chicken c-reactive protein (CRP) was found to be significantly changes on day 9, and the significant values in lipopolysaccharide (LPS) and monoamine oxidase (MAO) were found which respectively on the day 9 to 42 and 21; the diamine oxidase (DAO) changes were found after 42 days.The treatment diet of AGP and BT100 have affectedless histological changes in liver tissues than BT50 and NC. These findings suggested that BT could protect the chickens from the adverse impacts of Salmonella infection, andthese can be used as a feed additive to promote health and growth.